An integrated polymer/electrode interface for high performance ceramic/polymer electrolyte-based solid-state lithium batteries - Yan, Tingfang; Han, Songyi; Wu, Xiaomeng; Jia, Di; Chen, Yuhua; Tian, Wensheng; Wu, Yongmin; Zhu, Lei; Tang, Weiping (Applied physics letters, 2022)
Solid-state batteries (SSBs) are an ideal next-generation energy storage system due to their safety and high energy density. However, many interfacial problems, such as high interfacial resistance and poor compatibility between electrodes and electrolytes, limit the development of SSBs. In this study, an ultrathin interfacial layer composed of poly(ethylene oxide) (PEO) and ethylene carbonate (EC) are in situ fabricated on the surface of electrodes, integrating ceramic/polymer composite electrolyte and electrodes and reducing the interfacial impedance. Meanwhile, the excellent chemical compatibility between PEO and lithium metal effectively improves the interfacial stability. Also, the modification of the interfacial layer leads to more F- participation in the formation of solid electrolyte interphase (SEI), and the relative content of LiF, Li3N, and other by-products increases, which facilitates the formation of dense and stable SEI, thus inhibiting the growth of dendritic lithium and improving the ionic conductivity. With the interfacial layer, a highly stable interface against Li is maintained for more than 1400 h at a current density of 0.1 mA cm−2. A solid-state battery with LiNi0.5Co0.2Mn0.3O2 (NCM523) as the cathode delivers a capacity of 153.4 mAh g−1 and a capacity retention of 92.1% after 100 cycles. This study shows that the interfacial layer PEO-EC is an effective way to improve the performance of SSBs.